Evaluation of Subclinical Thyroidal Dysfunction with Gender- and Age-Specific Serum TSH Reference Intervals Derived from a 2014-2023 Ligurian Population - Giusti, Massimo; Sidoti, Marilena (British Journal of Healthcare and Medical Research, 2025)
Purpose: There is a need to refine the reference intervals (RI) of normal TSH values for age and gender. Aim of this study was to construct an RI of normal TSH in subjects living in Liguria, Italy. Methods: From 2014 to 2023, 1787 medical records (1336 females, 451 males) were evaluated in order to document TSH values. The RI of TSH was set at the 2.5th and 97.5th percentiles. The population was stratified into three age-groups: 18–44, 45–64 and ≥65 years. Results: Median TSH levels were significantly (P<0.0001) higher in females (1.82 mIU/l) than in males (1.43 mIU/l). This significance was maintained in all age-groups. In females, the RI were 0.46-6.31 mIU/l, 0.45-6.70 mIU/l, and 0.34-8.80 mIU/l in the 18-44 (n=542), 45-64 (n=517) and >65 (n=277) year age-groups. In males, the RI were 0.26-7.03 mIU/l, 0.33-6.21 mIU/l, and 0.26-8.57 mIU/l in the 18-44 (n=125), 45-64 (n=188) and >65 (n=138) year age-groups. When TSH values were evaluated by means of “study population RI” instead of the “pooled RI reported by manufacturers”, a significantly higher percentage of females had sub-clinical hyperthyroidism (P=0.005), while a significantly lower percentage of both females and males (females P<0.0001; males P=0.03) had sub-clinical hypothyroidism. Conclusions: This study establishes new gender- and age-specific RI for TSH in our area. These TSH RI could be extensively employed in order to improve diagnosis and treatments. The reduced percentages of sub-clinical hypothyroidism in the elderly when the RI was derived from the study population, rather than from RI from manufacturers, redefines the need for treatment.